A combination of Russell model and neutral DEA for3PL provider selection. (1st January 2012) - Azadi, Majid; Hosseinzadeh Zoroufchi, Kamyar; Farzipoor Saen, Reza
The main advantages of logistics partners are to allow the outsourcing company to focus on the principal competency, augment the efficiency, improve the service, reduce the transportation cost, restructure the supply chains and establish the marketplace legitimacy. Determining the appropriate third-party reverse logistics (3PL) provider is a crucial strategic consideration in supply chain management. One of the techniques that can be used for selecting 3PL provider is data envelopment analysis. The objective of this paper is to propose a combination of Russell model with neutral model for 3PL provider selection. A numerical example demonstrates the application of the proposed model.